2016
DOI: 10.4103/0972-3919.183616
|View full text |Cite
|
Sign up to set email alerts
|

A case report of hyperfunctioning metastatic thyroid cancer and rare I-131 avid liver metastasis

Abstract: Thyroid cancer is usually, relatively hypofunctional; most patients with thyroid cancer are clinically euthyroid. The combination of thyroid cancer and thyrotoxicosis is not common. We herein, report a case of follicular thyroid cancer with hyperfunctioning metastasis in a 43-year-old woman who presented with thyrotoxicosis, a cold right thyroid nodule, and low I-131 uptake at the thyroid bed. An additional total body scan with I-131 revealed a large radioiodine avid osteolytic bone metastasis with soft tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…Although most hyperfunctioning metastases are FTC-derived, metastases from PTC can also induce thyrotoxicosis (Danilovic et al 2015, Biyi et al 2016. The major sites of hyperfunctioning metastases are pulmonary and bone (Haq et al 2007, Nishihara et al 2010, Biyi et al 2016, and the rare metastases site of the liver was also reported (Takano et al 2006, Kunawudhi et al 2016. According to the study of Qiu, 0.71% DTC patients present with hyperfunctioning metastases, and the 10-year survival rate of patients with hyperfunctioning metastases was 65.79%, patients younger than 45 years at occurrence of distant metastases, those with only lung metastases, and patients with PTC had better prognoses (Qiu et al 2015).…”
Section: Hyperfunctioning Metastases Of Dtcmentioning
confidence: 99%
See 2 more Smart Citations
“…Although most hyperfunctioning metastases are FTC-derived, metastases from PTC can also induce thyrotoxicosis (Danilovic et al 2015, Biyi et al 2016. The major sites of hyperfunctioning metastases are pulmonary and bone (Haq et al 2007, Nishihara et al 2010, Biyi et al 2016, and the rare metastases site of the liver was also reported (Takano et al 2006, Kunawudhi et al 2016. According to the study of Qiu, 0.71% DTC patients present with hyperfunctioning metastases, and the 10-year survival rate of patients with hyperfunctioning metastases was 65.79%, patients younger than 45 years at occurrence of distant metastases, those with only lung metastases, and patients with PTC had better prognoses (Qiu et al 2015).…”
Section: Hyperfunctioning Metastases Of Dtcmentioning
confidence: 99%
“…Based on previous studies, the prescribed activity of 131 I to treat hyperfunctioning metastases of DTC varies from 13 mCi to 200 mCi (Tan et al 2009, Nishihara et al 2010, Kunawudhi et al 2016. Although there is no clear criterion for the dose of 131 I in treatment of functional metastases, it should be noted that high doses of 131 I could cause a large amount of tumor cell destruction, releasing a burst of thyroid hormones and causing thyrotoxic storm if the patients were not prepared adequately before and after 131 I treatment.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The scan showed multiple iodine-avid mediastinal and bilateral hilar lymph node, as well as lung and bone metastases. 2,4,7 Dosimetric analyses revealed a total 123 I uptake of 31.8% within the iodine-avid tumor lesions. First step, thyrostatic medication was initiated to treat the manifest hyperthyroidism.…”
mentioning
confidence: 96%
“…Contrary to the expectation, scintigraphy scan revealed a large area of increased nuclide uptake of the left thyroid lobe with almost complete suppression of the remaining parenchyma ( A2 ). Assuming that hyperfunctionality excludes malignancy with high probability, further clarification of the discrepant findings was warranted 2–5 . Fine-needle aspiration cytology yielded an equivocal result (group III) and could not contribute to the suspected diagnosis of thyroid cancer.…”
mentioning
confidence: 99%